Part 6: Formative and summative evaluation and action research. Issue 3 (1st December 2019) - Infante Mora, Eva
Abstract : Evaluation is essential to the analysis of the performance of academic programmes and is a central feature of the academic accountability movement. Most study abroad programmes, however, lack evaluation protocols, even though establishing them and acting on the results would contribute to their credibility. This final section of a comprehensive account of the reform of a study abroad programme presents how CASA-Sevilla has developed evaluation strategies to inform pedagogical changes in each successive semester to improve student-learning outcomes. The programme's aim is to achieve a 360-degree assessment by treating students holistically and including all involved faculty, staff, community partners and host families. The aim is also to be transparent in pointing out the problems in the programme's performance and use them as an impetus for improvement. This section is written to share what we have learned in hopes of starting a more robust dialogue among study abroad programmes about evaluation.